ASSESSING THE CONTRIBUTION OF EDUCATION TO GENDER WAGE DISPARITIES IN HIGH-EARNING PROFESSIONS - Jacobs , Jacobs; Jerry A, Jerry A (Journal of Current Research and Review (JCRR), 2022)
The gender wage gap has shown a significant reduction over the years due to increased educational attainment and women's entry into traditionally male-dominated professions. However, this overall decline masks the persistence of wage disparities among high earners. The unequal distribution of top earnings has contributed to the maintenance of the gender wage gap, with men benefiting the most from recent high-wage earnings gains. Moreover, gender gaps in college premiums and disparities in educational credentials have been linked to high-wage gender inequality. Understanding the stagnation of the wage gap among top earners requires examining the role of educational processes. This study investigates the contribution of gender differences in educational credentials to the high-wage earnings gap and explores the potential of changes in women's educational attainment to mitigate earnings disparities. The economic returns of higher education are influenced by the field of study, which is associated with individuals' professional opportunities. Despite women's advantage in bachelor's degree attainment, significant gender differences persist in fields of study. These disparities in fields of study contribute to wage inequality, particularly among high earners. Furthermore, graduate degrees play a crucial role in understanding top-end inequality. Although women have made strides in attaining advanced degrees, evidence suggests that gender inequality in the returns to these degrees persists, potentially limiting their impact on closing high-wage earnings gaps. This article assesses the extent to which gender disparities in field of study and advanced degrees explain the persistent gender wage gap among high-earning college-educated workers. Using microdata from the Census and American Community Survey, the analysis examines the contribution of these educational factors to gender inequality across the wage distribution. Decomposition models are employed to evaluate the influence of population differences in field of study and advanced degree attainment on gender wage gaps among high earners. The findings shed light on the mechanisms contributing to wage inequality dynamics in higher education and provide insights into whether changes in educational characteristics can help women overcome existing wage disparities. Ultimately, this research contributes to our understanding of the gender wage gap among college-educated individuals and informs policy and interventions aimed at promoting pay equity.